Oblicz wartości wyrażeń algebraicznych dla x=2
10-5x =
7+x do potęgi drugiej =
1-3x =
6(x-4)=
5(2x+1) =
7x - 6 =
x-3x=
6x + 4 =
2x - 5=
16:20:28
Oblicz wartości wyrażeń x=1/2
8x-6=
10x - 8 =
6-7x=
4(2x-1)=
5 (6 - 3x) =
7(10x + 4) =
16:21:20
x= -1
6x + 8 =
8 - 6x =
-6x + 7 =
2x - 5 =
1/2 x + 2 =

3

Odpowiedzi

2010-03-21T22:10:59+01:00
Oblicz wartości wyrażeń algebraicznych dla x=2

10 - 5x = 10 - 10 = 0
7 + x² = 7 + 2² = 7 + 4 = 11
1 - 3x = 1 - 6 = -5
6(x-4) = 6 - 2 = 4
5(2x+1) = 5 + 5 = 10
7x - 6 = 14 -6 = 8
x - 3x = 2 - 6 = -4
6x + 4 = 12 + 4 = 16
2x - 5 = 4 - 5 = -1
16:20:28
Oblicz wartości wyrażeń x=1/2
8x - 6 = 4 - 6 = -2
10x - 8 = 5 - 8 = -3
6 - 7x = 6 - 3,5 = 3,5
4(2x-1) = 4 - 1 = 3
5(6-3x) = 30 - 7,5 = 22,5
7(10x+4) = 35 + 4 = 39
16:21:20
x = -1
6x + 8 = -6 + 8 = 2
8 - 6x = 8 - (-6) = 14
-6x + 7 = 6 + 7 = 13
2x - 5 = -2 - 5 = -7
½x + 2 = -½ + 2 = 1,5
2010-03-21T22:11:06+01:00
0
81
-5
-12
25
8
-4
16
-1

-2
-3
2,5
0
22,5
63

2
14
13
-7
1,5
1 5 1
2010-03-21T22:15:00+01:00
10-5*2=10-10=0
7+2²=7+4=11
1-3*2=1-6=-5
6*2-24=12-24=-12
10*2+1=20+1=21
7*2-6=14-6=8
2-3*2=2-6=-4
6*2+4=12+4=16
2*2-5=4-5=-1


8*1/2-6=4-6=-2
10*1/2-8=5-8=-3
6-7*1/2=6-3,5=2,5
8*1/2-4=4-4=0
30-3*1/2=28,5
70*1/2+28=35+28=63

-6+8=2
8+6=14
6+7=13
-2-5=-7
-1/2+2=1i1/2
1 1 1